2011
DOI: 10.1177/1468796811398825
|View full text |Cite
|
Sign up to set email alerts
|

Black families and fostering of leadership

Abstract: Dominant depictions of Black families in US scholarship and political discourse have been negative; tropes of defunct, hyper-masculinized men and welfare queens along with a general 'tangle of pathology' indictment are common. This article supports other scholarship, which challenges these depictions and acknowledges common positive traits associated with Black families. Through an examination of interviews with 39 famous Black leaders from the US Civil Rights Era coupled with an extant review of sociological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Another study focused on minority female leaders in Pakistan, the United Kingdom as well as Brazil, who revealed through a set of qualitative interviews that they needed to deliberately plan to take more responsibility and engage in more roles before they could proceed to having leadership experiences 32 . Further studies have confirmed that the necessity for higher risk taking becomes apparent from an early age as future minority leaders are encouraged to respond to more opportunities by their families 30 as well as opt for more visible and diverse set of responsibilities throughout the school year 31 . Therefore, our second hypothesis can be formulated as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study focused on minority female leaders in Pakistan, the United Kingdom as well as Brazil, who revealed through a set of qualitative interviews that they needed to deliberately plan to take more responsibility and engage in more roles before they could proceed to having leadership experiences 32 . Further studies have confirmed that the necessity for higher risk taking becomes apparent from an early age as future minority leaders are encouraged to respond to more opportunities by their families 30 as well as opt for more visible and diverse set of responsibilities throughout the school year 31 . Therefore, our second hypothesis can be formulated as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, recent evidence from studies on female leadership and female ethnical minority leadership supports the validity of the separability assumption. Using qualitative interviews, these studies find that women leaders often make decisions to have multiple roles, take on many responsibilities, and diversify their efforts across several fields prior to engaging in leadership experiences in order to tackle gender and racial discrimination or to become more visible 13,14,30,31 .…”
Section: Stability Of Gender and Ethnical Background Identificationmentioning
confidence: 99%
“…That at the time, research among whites found the link between attitudinal motivation and intergenerational mobility to be tenuous (Hill and Ponza 1983), did not deter the application of this logic to American blacks. Ultimately, work in this nascent field revealed that far from the depiction of pathological and passive acquiescence to a blocked opportunity structure, most black families proactively groomed their youth to recognize the realities of racial and ethnic inequalities (Peters 1985; Stevenson 1994; Stevenson et al 2002; Strmic-Pawl and Leffler 2011). Given the impetus of this groundbreaking work, its limitations with regard to linking elders’ lessons on living with inequality to what could be conceptualized as ideological developments among youth are warranted.…”
Section: Personal Reflexive Statementmentioning
confidence: 99%
“…noninvolvement of Black parents (Dumas & Nelson, 2016;Houston et al, 2020;Kim & Hargrove, 2013), a growing list of scholars acknowledges the present and historical causes of the disparity in how deficit-based scholarship evaluates Black and white involvement in schooling (Warikoo & Carter, 2009) and instead focuses on those students who do achieve in academics (Delpit, 2012;Fries-Britt & Griffin, 2007;Griffin, 2006;Hampton, 2016;Strayhorn, 2009;Strmic-Pawl & Leffler, 2011) and Black parents who are intentionally engaged in their children's education (Allen & White-Smith, 2018;Posey-Maddox, 2017;Posey-Maddox et al, 2021;Rollock et al, 2015;Toldson & Lemmons, 2013).…”
mentioning
confidence: 99%